Analysis of the fishery of the mamgrove clams Anodontia edentula (Linnaeus, 1758) and Austriella corrugata (Deshayes, 1843) in Tarangnan, Samar using the value chain framework and some aspects of their ecology and biology. - Carcellar, Welmen B.
Mangrove clams inhabit the mangrove mudflats in Barangay Bahay, Tarangnan, Samar. Two species have been identified as anodontia edentula and Austriella corrugata. The two mangrove clam species display the morphological characteristics of lucinids and differ only in external shell morphology and ligament position. These mangrove clams are a source of food and income for gleaners and are highly prized in the Philippines for their flavor and their large size. The exploitation of A. edentula and A. corrugata was very prominent since the 1960s and resulted in resource depletion due to the poor understanding of its fishery, ecology, and biology directly resulting in a lack of management. The present study (1) investigated the value chain of A. corrugata and A. edentula, (2) characterized the habitat, population density, and co-inhabitants; and (3) described the shell morphology, sex, and feeding biology. Interviews and observations were conducted to analyze the value chain of the mangrove clam fishery. results showed that (1) gleaners were mostly male and vendors were mostly female; (2) the wet market retailers had the highest net income in the mangrove clam trade; and (3) the lack of support from the local government and other stakeholders to the enablers and lack of enforcement impede the development of the mangrove clam fishery. The physicochemical parameters showed that the mangrove clams inhabit a marine environment and a sandy-muddy substrate, buried at 20-65 cm deep and collected through bare hands by gleaner. The shell morphology was investigated using geometric measurement and revealed that the posterior angle and growth lines of A. corrugata are more prominent compared to A. edentula which has finer growth lines while the sex of the clams was determined through histological analysis and revealed that both were dioecious species. The pre-ingested food and plankton in water were determined qualitatively and results showed that the mangrove clams mainly relied primarily on diatoms for food. Moreover, to fortify management policies, population dynamics, post-harvest technologies, and more aquaculture studies are recommended.